The effectiveness of green certificates - evidence from Poland - Mazurkiewicz, J. (Економічний вісник Донбасу, 2016)
The paper examines the role of technological and institutional lock-in as a barrier to more sustainable innovation in the energy sector, and the implications of this to for determining appropriate policy responses. The paper, with theoretical input from path-dependency, technology and carbon lock-in as well as innovation effect of deployment policies, presents a qualitative study of the factors that influenced the evolution of tradable green certificates in Poland.The path dependency has been reinforced by the lock-in mechanisms: economies of scale, economies of scope, network externalities and informational increasing returns. Hence, the characteristics of current regime set the conditions for the development of new transition pathways. The incumbent socio-technical regime is not just fossil-based, but may also include mature niches specialised in the exploitation of renewable sources. This implies a need to distinguish between lock-in mechanisms favouring the old fossil-based regime, well-established (mature) renewable energy niches, or new pathways. It also provides the justification for intervention in the process of technology diffusion: the greater ability of the state to coordinate technological choices undertaken in the frame of market mechanism.